2021
DOI: 10.3389/fcimb.2021.753721
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ACE2 Polymorphisms on COVID-19 Disease: Susceptibility, Severity, and Therapy

Abstract: The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has currently spread worldwide, leading to high morbidity and mortality. As the putative receptor of SARS-CoV-2, angiotensin-converting enzyme 2 (ACE2) is widely distributed in various tissues and organs of the human body. Simultaneously, ACE2 acts as the physiological counterbalance of ACE providing homeostatic regulation of circulating angiotensin II levels. Given that some ACE2 variants are known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 58 publications
3
35
0
1
Order By: Relevance
“…Specifically, excluding internal causes gives further strength to the theories that identify COVID-19 as the principal cause of such a tragic scenario. COVID-19 dangerousness is confirmed at the molecular-genetic level [24]: compared to its predecessor, SARS-CoV-2 binds to the ACE2 peptidase domain two-four times more strongly, which increases its severity [25][26][27]. Besides, our results statistically support the greater virulence and mortality of COVID-19 in northern Italy and towards the male population [28][29][30].…”
Section: Main Findingssupporting
confidence: 68%
“…Specifically, excluding internal causes gives further strength to the theories that identify COVID-19 as the principal cause of such a tragic scenario. COVID-19 dangerousness is confirmed at the molecular-genetic level [24]: compared to its predecessor, SARS-CoV-2 binds to the ACE2 peptidase domain two-four times more strongly, which increases its severity [25][26][27]. Besides, our results statistically support the greater virulence and mortality of COVID-19 in northern Italy and towards the male population [28][29][30].…”
Section: Main Findingssupporting
confidence: 68%
“…REGN-COV2 provided benefits in trials with rhesus macaques and golden hamsters, simulating mild and severe disease, respectively, enhancing viral clearance, and was released by some national health agencies for emergency use, such as Anvisa, the Brazilian agency (Baum et al, 2020; Weinreich et al, 2021). LY-CoV555, another promising neutralizing antibody that entered clinical evaluation, was also studied in a cocktail form with LY-CoV016 (P. Chen et al, 2021; Renn et al, 2020; Starr et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we extended our previous in silico study (Giron et al, 2020) to investigate and compare the impact of these mutations on the interaction between the RBD and the human ACE2 since this is the very first step for the SARS-CoV-2 cellular entry. ACE2 polymorphisms were also included in our analysis as they were suggested to be a genetic factor that could affect the viral entry independently, but also the severity of the disease due to its role in comorbidities, such as hypertension (F. Chen et al, 2021; Möhlendick et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the coordinates of ACE2 crystal structure were obtained from the protein data bank (PDB), PDB ID 6M17, excluding the coordinates of receptor binding domain (RBD) of SARS-CoV2 from the co-complexed B o AT1 dimer. I-TASSER was used to model the missing C terminal residues (769 to 805) and N terminal residues (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) of the ACE2 transmembrane helices (25). SWISS-MODEL was used to generate the three-dimensional homology models of mutant proteins using modeled full-length structure of ACE2 as a template (26).…”
Section: Methodsmentioning
confidence: 99%
“…By the beginning of the spread of COVID-19 infection in 2019, Cao et al and other groups have demonstrated that ACE2 expression levels and genetic variation may in uence its interaction with the SARS-CoV-2 spike S-protein (8,12,13). Therefore, the highlighted variable outcomes may explain some of the interindividual variability of the infection onset, susceptibility, and severity (9).…”
Section: Introductionmentioning
confidence: 99%